The importance of the jubilee mall on the KNUST community, perspective of stakeholders. - YVONNE NAA ADZANE OKAI (KNUST, 2025)
A Thesis Submitted In Partial Fulfilment Of The Award Of The Degree Of Master Of Business Administration (Strategic Management And Consulting).